If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x) * m + (5x + 1) * m + (5x + 3) * m = 180 Remove parenthesis around (4x) 4x * m + (5x + 1) * m + (5x + 3) * m = 180 Multiply x * m 4mx + (5x + 1) * m + (5x + 3) * m = 180 Reorder the terms: 4mx + (1 + 5x) * m + (5x + 3) * m = 180 Reorder the terms for easier multiplication: 4mx + m(1 + 5x) + (5x + 3) * m = 180 4mx + (1 * m + 5x * m) + (5x + 3) * m = 180 4mx + (1m + 5mx) + (5x + 3) * m = 180 Reorder the terms: 4mx + 1m + 5mx + (3 + 5x) * m = 180 Reorder the terms for easier multiplication: 4mx + 1m + 5mx + m(3 + 5x) = 180 4mx + 1m + 5mx + (3 * m + 5x * m) = 180 4mx + 1m + 5mx + (3m + 5mx) = 180 Reorder the terms: 1m + 3m + 4mx + 5mx + 5mx = 180 Combine like terms: 1m + 3m = 4m 4m + 4mx + 5mx + 5mx = 180 Combine like terms: 4mx + 5mx = 9mx 4m + 9mx + 5mx = 180 Combine like terms: 9mx + 5mx = 14mx 4m + 14mx = 180 Solving 4m + 14mx = 180 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Reorder the terms: -180 + 4m + 14mx = 180 + -180 Combine like terms: 180 + -180 = 0 -180 + 4m + 14mx = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-90 + 2m + 7mx) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-90 + 2m + 7mx)' equal to zero and attempt to solve: Simplifying -90 + 2m + 7mx = 0 Solving -90 + 2m + 7mx = 0 Move all terms containing m to the left, all other terms to the right. Add '90' to each side of the equation. -90 + 2m + 90 + 7mx = 0 + 90 Reorder the terms: -90 + 90 + 2m + 7mx = 0 + 90 Combine like terms: -90 + 90 = 0 0 + 2m + 7mx = 0 + 90 2m + 7mx = 0 + 90 Combine like terms: 0 + 90 = 90 2m + 7mx = 90 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 5w+4(3+w)=66 | | 11.3e-10.1e+7=13.24 | | 425/68=150/x | | 53a-79=26a+29 | | 106/4=x/12 | | =x^2+10x+9 | | 5x(-1)=10 | | X+1=5x-1 | | 53a-7.9=26a+29 | | 3/5(z-3)-11/5=-4 | | 7+2y=3.4 | | V/10.44-2.8=-4.422 | | X^2-9x^2+18=0 | | -5u+3(u+5)=29 | | Lnx^3/x^6 | | 14.63/9.315 | | 34z+63=-17z+471 | | 2/3(z-2)-11/3=-5 | | 5x+33=98 | | 10-10d=20 | | 2v=21 | | -80+-4x=120+6x | | (x+1)(x-1)=(x+1)(x-2) | | -80x+-4x=120+6x | | 3x-19=-70 | | 23-5=110 | | -(6y+1)-(-5y-8)=0 | | 3x^2-24x+28=0 | | 83overx=7 | | 3h-7=-7 | | -2(x-2)=-4x+14 | | -5-(-5/2) |